A contribution to the centipede fauna of Venezuela (Chilopoda: Scolopendromorpha) - Schileyko, Arkady A. (Zootaxa, 2014)
The descriptions of twelve Venezuelan Scolopendromorpha, a list of species, identification key and detailed list of localities are presented. Cryptops (C.) venezuelae Chamberlin, 1939, known only from the holotype has been re-described and Scolopendra conjungens Muralewicz, 1913 reduced to a junior synonym of Scolopendra angulata Newport, 1844 syn. nov.